Bio-economic modelling for better quantification of agriculture environmental impacts - Deybe D. (Comprehensive economic and spatial bio-energy modelling, 2002)
Agriculture activity is necessary to satisfy human food demand, but it also implies disturbances of natural resources equilibrium. These disturbances can imply resource depletion due to ill-management and thus have negative impacts on the environment. However, in most cases the effects can only be observed in the long-term and farmers do not always consider them when making their decisions. Besides, most policy measures do not take into consideration these impacts and induce farmers reactions that might jeopardise future generations well-being. It is necessary to simulate alternative policy scenarios and evaluate their impact in the short and in the long-term in order to help policy makers.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)